Piezo-phototronic mediated enhanced photodetection characteristics of plasmonic Au-g-C3N4/CdS/ZnO based hybrid heterojunctions on a flexible platform. Issue 40 (10th October 2018) - Pal, Sourabh; Bayan, Sayan; Ray, Samit K.
Abstract : We have studied the piezo-phototronic induced enhancement in the photo-response of CdS/ZnO heterojunctions attached with plasmonic Au nanoparticle loaded 2D-graphitic carbon nitride (g-C3 N4 ). Abstract : We have studied the piezo-phototronic induced enhancement in the photo-response of CdS/ZnO heterojunctions attached with plasmonic Au nanoparticle loaded 2D-graphitic carbon nitride (g-C3 N4 ). The hybrid g-C3 N4 /CdS/ZnO heterojunction favours the charge carrier separation through the formation of a step-like band alignment. Furthermore, the integration of plasmonic Au loaded g-C3 N4 nanosheets on the conventional CdS/ZnO heterojunction facilitates improved visible light absorption properties. The heterojunction device on a flexible platform under the application of a strain (∼0.017%) exhibits ∼10 2 times higher photoresponse over the control sample at a constant bias of ∼2 V. The variation in the photo-response under different bending conditions has been explained in terms of the improved charge transport through the modified energy bands at the interface of ZnO. The improved piezo-phototronic properties originated from the plasmonic properties of Au loaded g-C3 N4 and the piezoelectric characteristics of c -axis oriented ZnO films may be used for future flexible photonic devices.